An Analysis of Tasks of Nurses Caring for Patients with COVID-19 in a Nationally-Designated Inpatient Treatment Unit. - Jung Minho; Kim Moon-Sook; Lee Joo-Yeon; Lee Kyung Yi; Park Yeon-Hwan (Journal of Korean Academy of Nursing, 2022)
Purpose: The purpose of this study was to provide foundational knowledge on nursing tasks performed on patients with COVID-19 in a nationally-designated inpatient treatment unit. Methods: This study employs both quantitative and qualitative approaches. The quantitative method investigated the content and frequency of nursing tasks for 460 patients (age ≥ 18 y, 57.4% men) from January 20, 2020, to September 30, 2021, by analyzing hospital information system records. Qualitative data were collected via focus group interviews. The study involved interviews with three focus groups comprising 18 nurses overall to assess their experiences and perspectives on nursing care during the pandemic from February 3, 2022, to February 15, 2022. The data were examined with thematic analysis. Results: Overall, 49 different areas of nursing tasks (n = 130,687) were identified based on the Korean Patient Classification System for nurses during the study period. Among the performed tasks, monitoring of oxygen saturation and measuring of vital signs were considered high-priority. From the focus group interview, three main themes and eleven sub-themes were generated. The three main themes are "Experiencing eventfulness in isolated settings," "All-around player," and "Reflections for solutions." Conclusion: During the COVID-19 pandemic, it is imperative to ensure adequate staffing levels, compensation, and educational support for nurses. The study further propose improving guidelines for emerging infectious diseases and patient classification systems to improve the overall quality of patient care.